Healthiness of foods and non-alcoholic beverages according to store type: A population-based study of household food and drink purchases in New Zealand - Essa Tawfiq; Kathryn E. Bradbury; Cliona Ni Mhurchu (Elsevier, 2021)
Background: Obesity and diet-related noncommunicable diseases (NCDs) account for the largest proportion of disease burden worldwide, and an unhealthy food environment is a key driver. Food retailers play an important role in food environments through the availability and purchases of healthy food products at various stores. Objectives: To assess whether the healthiness of food and non-alcoholic drink product purchases vary according to retail store type. Methods: We undertook a cross-sectional analysis of Nielsen New Zealand Homescan® panel data, which is a nationally representative sample of 2500 households in terms of certain key household demographic and socioeconomic characteristics. Panel members were asked to record all food and beverage products that were purchased and brought back to the home between October 2018 and October 2019. Household food and non-alcoholic drink purchases were linked with two food composition databases (Nutritrack, a New Zealand packaged food composition database, and the FOODfiles New Zealand Food Composition Database) to extract data on the nutrient profile of products purchased. We developed a store classification tool, and classified stores as supermarkets, grocery stores, convenience stores, fruit and vegetable stores, meat and fish stores, or bakeries. We estimated the Health Star Rating (HSR) for all products and defined a product with HSR ≥ 3.5 as 'healthy'. We computed estimated mean HSR and conducted multivariate regression analyses. Results: In total, 3,940,458 product purchases were included in the analyses, consisting of 20,491 unique products purchased at different stores over the one-year period by 1800 panellist households. Supermarket products made up the majority of household food and drink purchases (3,545,141 of 3,940,458; 90%). Overall, the estimated mean HSR was 3.5 stars. In comparison to the reference group of supermarkets, the odds ratio for healthy products purchased at fruit and vegetable stores was 4.62, at grocery stores it was 2.36, and at meat and fish stores it was 1.99. In contrast, the odds ratios from convenience stores and bakeries were 0.58 and 0.03. Except for convenience stores, these differences were statistically significant (p < 0.05). Discussion: We found significant differences in household purchases of healthy food and beverages according to food retail store type, with healthier food much more likely to be purchased from fruit and vegetable stores, meat and fish stores and grocery stores, and much less likely to be purchased from bakeries and convenience stores as compared with supermarkets. Conclusion: Policies to improve healthy food retailing should consider all retail store types and focus particularly on increasing the availability of healthy food options at convenience stores and bakeries. Given that supermarkets are the source of most household food purchases (both healthy and unhealthy), strategies are also warranted to increase the relative availability and purchases of healthy foods from supermarkets.